Malawi : Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines the Staff-Monitored Program (SMP) for Malawi. The authorities have requested staff monitoring of their macroeconomic program for the 2004/05 fiscal year (June-July) with a view to establishing a performance track record that could lead to a new Poverty Reduction and Growth Facility (PRGF) arrangement. The main objectives of the SMP will only be achieved if the approved 2004/05 (June-July) budget is in line with the agreed budget framework and the monetary overhang is addressed. Structural measures under the SMP will focus on public expenditure management.